First identification of N-trans-feruloyltyramine as a key α-glucosidase inhibitor from Piper sarmentosum fruits - Yodsawad, Thita; Doungwichitrkul, Titiruetai; Tantiwatcharachai, Pattraporn; Nguyen, Anh–Khoa; Phuwapraisirisan, Preecha (Agriculture and Natural Resources, 2024)
Importance of the work: Piper sarmentosum is used as an herb and in traditional medicine for diabetes treatment. This was the first report of the isolation of α-glucosidase inhibitors from P. sarmentosum fruits. Objectives: To isolate and identify the bioactive compounds from the fruits of P. sarmentosum and to evaluate their α-glucosidase inhibition. Materials and Methods: The CH2Cl2 and acetone extracts were separated and purified using various chromatographic techniques. The structures of the compounds were determined based on spectroscopic data (nuclear magnetic resonance and mass spectrometry) and compared with other reported data. The levels of α-glucosidase inhibitory activity of the isolated compounds were assessed using a colorimetric method, with acarbose serving as a positive control. Results: In total, 10 known compounds were identified: sarmentamide A (1), sarmentamide B (2), deacetylsarmentamide B (3), (3S,4R)-3,4,5-trihydroxypentanoic acid 1,4-lactone (4), N-trans-feruloyltyramine (5), (1E,3S)-1-cinnamoyl-3-hydroxypyrrolidine (6), sarmentosine (7), chaplupyrrolidone A (8), piperlotine-A (9) and coumaric acid (10). The phenylpropanamides 1, 3 and 5 prodcued weak-to-moderate inhibitory activity against both sucrase and maltase, with half maximal inhibitory concentration (IC50) values in the range 0.28–9.48 mM. Phenylpropanamide 6 inhibited only sucrase (IC50 value of 0.93 mM), whereas phenylpropanamide 2 and lactone 4 inhibited only maltase (IC50 values of 6.16 mM and 9.26 mM, respectively). Alkyl amide 7 and the phenylpropanamides 8 and 9, as well as phenylpropanoid 10 produced no inhibition. Main finding: The phenylpropanamides contained more α-glucosidases than the alkyl amide, lactone and phenylpropanoid. P. sarmentosum fruits could be regarded as a potential source of α-glucosidase inhibitors. Further investigation into the inhibitory mechanisms could pave the way for their appropriate utilization in pharmaceutical applications.